A study of accountability practice in Dompet Dhuafa Waqf of Indonesia - Ihsan, Hidayatul; Sulaiman, Maliah; Mohd Alwi, Norhayati; Adnan, Muhammad Akhya (King Abdulaziz University, 2017)
The aim of this study is to address the issue of accountability practice in a waqf institution. Specifically, the focus of this study is to provide insights into how accountability is perceived and discharged by the mutawallī (waqf trustee) in managing a waqf. In so doing, a case study of one Indonesian waqf institution, that is, Dompet Dhuafa is undertaken. To achieve the stated objectives of the study, the researchers used various techniques of data collection that mainly comprises: interviews, observations and reviews of documents. The findings reveal that the belief in dual accountability – to Allah and human beings – has strengthened the mutawallī’s perception concerning the importance of accountability. Moreover, in showing its accountability in managing a waqf to stakeholders, the mutawallī uses various mechanisms. In addition, the mutawallī is also liable to discerning accountability to himself/herself. Hence, this study concludes that the holistic accountability practiced by Dompet Dhuafa is an integrative process. It does not only encompass fulfilling upward and downward accountabilities, but also involves the commitment to preserve organizational values.